이산화망간 촉매와 오존을 이용한 NO의 촉매 산화 특성 - 진성민; 정종수; 이재헌; 정주영 (한국환경과학회, 2009)
In this study, the fundamental experiments were performed for catalytic oxidation of NO (50 ppm) on MnO2 in the presence of ozone. The experiments were carried out at various catalytic temperatures (30-120℃) and ozone concentrations (50-150 ppm) to investigate the behavior of NO oxidation. The honeycomb type MnO2 catalyst was rectangular with a cell density of 300 cells per squuare inch. Due to O3 injection, NO reacted with O3 to form NO2, which was adsorbed at the MnO2 surface. The excessive ozone was decomposed to O* onto the MnO2 catalyst bed, and then that O* was reacted with NO2 to form NO3-. It was found that the optimal O3/NO ratio for catalytic oxidation of NO on MnO2 was 2.0, and the NO removal efficiency on MnO2 was 83% at 30℃. As a result, NO was converted mainly to NO3-.